Cerebral Gray Matter Volume Reductions in Dyslexics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Brain MR images were compared in 16 right-handed men (mean age, 24 years; range 18 to 40) with dyslexia and 14 control subjects using a voxel-based analysis, at Stanford University School of Medicine, CA.